25.1 Vepsän kel': ELDIA lühetud raport (tegonsatuž) - Grünthal, Riho; Puura, Ulriikka; Zajceva, Nina; Karjalainen, Heini
Veps-language summary of the case study on the Veps language in Russia, conducted within the EU-FP7 research project ELDIA